Optimalisasi Teknologi Komunikasi Informasi Command Center Bagi Efektifitas Tenaga Kesejahteraan Sosial Kecamatan - Rio Febriannur Rachman (Institut Agama Islam Syarifuddin Lumajang, 2019)
Surabaya has many problems with Social Welfare Problems (Penyandang Masalah Kesejahteraan Sosial or PMKS). The existence of the District Social Welfare Workers (Tenaga Kesejahteraan Sosial Kecamatan or TKSK) or social volunteers formed by the Ministry of Social Affairs has a central role in eradicating this problem. In 2016, when the Command Center 112 was launched by the Surabaya City Government, with the use of communication and information technology, TKSK was also given access to receive information from there. Interestingly, TKSK in each district has a good relationship with those in other districts. So, they can help each other when running errands. Keywords: Technology, Communication, Volunteers, Surabaya City Government